1999
DOI: 10.1063/1.123996
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence study of CdTe/ZnTe self-assembled quantum dots

Abstract: We report on optical properties of CdTe self-assembled quantum dots ͑SADs͒ grown by molecular beam epitaxy on ZnTe. Formation of SADs was achieved by deposition of 1.5-2.5 monolayers of CdTe at a substrate temperature of 420°C and by applying growth interrupts for few seconds in Cd flux. The resulting dots have a typical diameter of 2 nm and a sheet density of 10 12 cm Ϫ2 . At Tϭ2 K the photoluminescence ͑PL͒ spectra consist of two emission lines. The high-energy line originates from excitonic recombination in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
1
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 153 publications
(96 citation statements)
references
References 13 publications
6
86
1
1
Order By: Relevance
“…2.2-(b)) within the same temperature region where the peak position exhibits a red shift relative to the bandgap ( Fig. 2-(c)); this means that one is dealing with an ensemble of such low dimensional structures (Brusaferri et al, 1996;Sanguinetti et al, 1999;Karczewski et al, 1999). It is more important that the careful analysis of the green band peak position at various excitation intensities showed that it increases linearly with the cubic root of excitation intensity (the lower inset in Fig.…”
Section: Photoluminescence Characterizationmentioning
confidence: 99%
“…2.2-(b)) within the same temperature region where the peak position exhibits a red shift relative to the bandgap ( Fig. 2-(c)); this means that one is dealing with an ensemble of such low dimensional structures (Brusaferri et al, 1996;Sanguinetti et al, 1999;Karczewski et al, 1999). It is more important that the careful analysis of the green band peak position at various excitation intensities showed that it increases linearly with the cubic root of excitation intensity (the lower inset in Fig.…”
Section: Photoluminescence Characterizationmentioning
confidence: 99%
“…Two sam- * corresponding author; e-mail: Tomasz.Kazimierczuk@fuw.edu.pl ple growth procedures were used. The first studies on non-resonant excitation mechanisms were performed on dots formed with growth-interrupt method [6]. More advanced experiments under non-resonant and quasi--resonant regime were done on dots grown with amorphous tellurium technique described in Ref.…”
Section: Samples and Experimentsmentioning
confidence: 99%
“…In particular, in telluride systems, good optical properties can be obtained for CdTe QWs embedded in (Cd,Mg)Te barriers, and CdTe QDs in ZnTe barriers. However emission energy of such QWs is about 1.6 eV [18], and about 2 eV for QDs [19]. Moreover ZnTe barrier exhibit much smaller lattice parameter than CdTe or (Cd,Mg)Te.…”
Section: Introductionmentioning
confidence: 99%